Characteristic flight speeds in bats - Bullen, R. D.; McKenzie, N. L.; Cruz-Neto, A. P. [UNESP] (Springer Nature, 2016)
We present empirical data on flight speed for 30 species of Australian bats representing seven families. These data show five characteristic level flight speeds: ‘minimum’ (Vmin), ‘best efficiency’ (Veff), ‘most common’ (Vmode), ‘maximum cruise’ (Vmcr) and ‘maximum spurt’ (Vmsp). Next, we calculate Vmin, Veff, ‘maximum aerobic’ (Vae), ‘sustainable anaerobic’ (Vsan) and ‘maximum anaerobic’ (Vman) flight speeds using a published quasi-steady model. Model predictions were within 0.5 m s−1 of the empirical values for all five characteristic speeds given adequate samples. Model fidelity was cross-checked using flight speed data published for other Old and New World species.
Keywords: Aerodynamics; Bat; Flight; Speed